Influencing Factors of Multiplayer Online Battle Arena (MOBA) Game Player’s Behavior in Jakarta - Aprilia, Nurrafa; Indika, Deru R. (Business and Entrepreneurial Review, 2025)
MOBA game is currently one of the most popular subgenres that can be played for free by anyone anywhere. With a wide player segment in Indonesia, a lot of player pays to play the game, and with a high buying rates on pandemic era in 2020. This study aims to examine the influence of antecedent factor to behavior intention among MOBA game players that impacted the user behavior in Jakarta. The result shows that from the seven factors of antecedent behavior, escapism, role projection, enjoyment, arousal, and sensory experience are the factors that affected player’s behavior intention while fantasy and emotional involvement are not a relevant factor for DKI Jakarta players.